MOF derived Mn/CeO2 nanozymes with oxidase-like and ultra-high peroxidase-like activity for TAC detection in food samples - Zeyi Guo; Jia You; Jiaxin He; Xiao Xu; Yafei Xue; Shiyun Ai; Lulu Cui; Houshen Li; Shuhong Sun (Food Chemistry: X, 2025)
Despite significant advances in nanozyme engineering, achieving high catalytic activity remains a critical challenge. In this work, a series of Mn-doped CeO2 nanozymes with oxidase (OD)-like and ultra-high peroxidase (POD)-like activity were synthesized by MOF-derived strategy. The strong MnCe interaction, originating from Mn2+ coordination in the Ce-MOF precursor, contributes to their superior catalytic performance. The TAC sensors constructed based on the dual enzyme-like activities of Mn4.68/CeO2 nanozyme demonstrated exceptional detection performance for antioxidants. Both sensor systems exhibited excellent linear correlations between absorbance and antioxidant concentration (R2 = 0.9776–0.9978), along with high selectivity toward various antioxidants. Notably, the POD-like activity-based sensor demonstrated comparable performance to the standard method in the analysis of food samples, with measured AA recoveries of 101.2 % (100 μM spike) and 97.0 % (700 μM spike). This work provides both a practical analytical platform and a generalizable strategy for high-activity bimetallic nanozyme design.